Students’ Interest in Speaking English and How It relates to Their Speaking Achievement - Najoan, Lifely Juwita; Sinadia, Alfrits Roul (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Klabat, 2024)
Abstract The background of this research was the need to investigate the interest in speaking English and speaking English achievement. It mainly aimed to study the relationship between the two variables. The study was quantitative research using descriptive, inferential, correlational, and survey methods conducted upon students at a private senior high school. The findings of the study showed that the students are interested in speaking English and that their English-speaking achievement is good. The last finding showed that there is a correlation between the students’ interest in speaking English and their English-speaking achievement. Keywords—interest, achievement, interest in speaking, speaking achievement Abstrak Latar belakang penelitian ini adalah perlunya diteliti minat berbicara bahasa Inggris dan prestasi berbahasa Inggris. Ini terutama bertujuan untuk mempelajari hubungan antara kedua variabel. Penelitian ini merupakan penelitian kuantitatif dengan menggunakan metode deskriptif, inferensial, korelasional, dan survei yang dilakukan pada siswa sebuah sekolah menengah atas swasta. Temuan penelitian menunjukkan bahwa siswa tertarik untuk berbicara bahasa Inggris dan bahwa prestasi berbahasa Inggris mereka baik. Temuan terakhir menunjukkan bahwa ada korelasi antara minat siswa dalam berbicara bahasa Inggris dan prestasi berbahasa Inggris mereka. Kata kunci—minat, prestasi, minat berbicara bahasa Inggris, prestasi berbicara bahasa Inggris